Variability of winter and summer surface ozone in Mexico City on the intraseasonal timescale - B. S. Barrett; B. S. Barrett; G. B. Raga (Atmospheric Chemistry and Physics, 2016)
Surface ozone concentrations in Mexico City frequently exceed the Mexican standard and have proven difficult to forecast due to changes in meteorological conditions at its tropical location. The Madden–Julian Oscillation (MJO) is largely responsible for intraseasonal variability in the tropics. Circulation patterns in the lower and upper troposphere and precipitation are associated with the oscillation as it progresses eastward around the planet. It is typically described by phases (labeled 1 through 8), which correspond to the broad longitudinal location of the active component of the oscillation with enhanced precipitation. In this study we evaluate the intraseasonal variability of winter and summer surface ozone concentrations in Mexico City, which was investigated over the period 1986–2014 to determine if there is a modulation by the MJO that would aid in the forecast of high-pollution episodes. Over 1 000 000 hourly observations of surface ozone from five stations around the metropolitan area were standardized and then binned by active phase of the MJO, with phase determined using the real-time multivariate MJO index. Highest winter ozone concentrations were found in Mexico City on days when the MJO was active and in phase 2 (over the Indian Ocean), and highest summer ozone concentrations were found on days when the MJO was active and in phase 6 (over the western Pacific Ocean). Lowest winter ozone concentrations were found during active MJO phase 8 (over the eastern Pacific Ocean), and lowest summer ozone concentrations were found during active MJO phase 1 (over the Atlantic Ocean). Anomalies of reanalysis-based cloud cover and UV-B radiation supported the observed variability in surface ozone in both summer and winter: MJO phases with highest ozone concentration had largest positive UV-B radiation anomalies and lowest cloud-cover fraction, while phases with lowest ozone concentration had largest negative UV-B radiation anomalies and highest cloud-cover fraction. Furthermore, geopotential height anomalies at 250 hPa favoring reduced cloudiness, and thus elevated surface ozone, were found in both seasons during MJO phases with above-normal ozone concentrations. Similar height anomalies at 250 hPa favoring enhanced cloudiness, and thus reduced surface ozone, were found in both seasons during MJO phases with below-normal ozone concentrations. These anomalies confirm a physical pathway for MJO modulation of surface ozone via modulation of the upper troposphere.